MRI sebagai Modalitas Diagnosis Miokarditis pada Pasien dengan Nyeri Dada : Serial Kasus - Prasetyo Andriono; Armand Achmadsyah (Cermin Dunia Kedokteran, 2025)
Myocarditis is the inflammation of the cardiac muscle. Diagnosis can be challenging as the symptoms are not typical. Cardiac magnetic resonance imaging (MRI) can be used to diagnose myocarditis, allows more reliable quantitative measurements, and a clear discrimination from other mimicking conditions. We include 3 patients with myocarditis.